Metagenomic Characterization of Intestinal Regions in Pigs With Contrasting Feed Efficiency - Quan, Jianping; Wu, Zhenfang; Ye, Yong; Peng, Longlong; Wu, Jie; Ruan, Donglin; Qiu, Yibin; Ding, Rongrong; Wang, Xingwang; Zheng, Enqin; Cai, Gengyuan; Huang, Wen; et al. (Frontiers in Microbiology, 2020)
Greater feed efficiency (FE) is critical in increasing profitability while reducing the environmental impact of pig production. Previous studies that identified swine FE-associated bacterial taxa were limited in either sampling sites or sequencing methods. This study characterized the microbiomes within the intestine of FE contrasting Duroc× (Landrace×Yorkshire) (DLY) pigs with a comprehensive representation of diverse sampling sites (ileum, cecum and colon) and a metagenomic sequencing approach. A total of 226 pigs were ranked according to their feed efficiency between weaning to140 day old, and six with extreme phenotypes were selected, three for each of the high and low groups. The results revealed that the cecum and colon had similar microbial taxonomic composition and function, and had higher capacity in polysaccharide metabolism than the ileum. We found in cecum that the high FE pigs had slightly higher richness and evenness in their micriobiota than the low FE pigs. We identified 12 phyla, 17 genera and 39 species (e.g., Treponema porcinum, Treponema bryantii and Firmicutes bacterium CAG:110) that were potentially associated with swine FE variation in cecum microbiota through LEfSe analysis. Species enriched in the cecum of the high FE pigs had a greater ability to utilize dietary polysaccharides and dietary protein according to the KEGG annotation. Analysis of antibiotic resistance based on the CARD database annotation indicated that the macB resistant gene might play an important role in shaping the microbial community in the cecum of pigs with contrasting FE. The bacteria from the genus Prevotella was highly enriched in the cecum of low FE pigs, which may impair the establishment of a more effective nutrient harvesting microbiota because of the interaction between Prevotella and other benefical microbes. These findings improved our understanding of the microbial compositions in the different gut locations of DLY pigs and identified many biomarkers associated with FE variation wich may be used to develop strategies to improve FE in pigs.